Perception of Undergraduate Dental Students About the Advantages and Disadvantages of Distance Education During the COVID-19 Pandemic - Hasani, Ahmad; Namdari, Mahshid; Kasraei, Shahin; Madihi, Saeed (Journal of Dental School, 2022)
Objectives The present study aimed to assess the dental students’ perception about distance education during the coronavirus disease-2019 (COVID-19) pandemic. Methods An analytical cross-sectional study was done on 288 dental students from Shahid Beheshti and Mashhad Universities of Medical sciences in February 2022. A standardized, electronic questionnaire was used for data collection. The questionnaire included a comparison of pros and cons of distance and in-person education and the NAVID system with online video lectures. The content validity of the questionnaire was assessed by qualitative and quantitative validation tools. The Chi-square test was used to compare the advantages and disadvantages of distance learning. Online video lectures and the NAVID system were compared by the Wilcoxon signed rank test. Results Totally, 288 students (141 females and 147 males) completed the online questionnaire. Instant access to online sources was the most essential advantage of e-learning (74.7%), and the most critical disadvantages were lack of student-tutor (50.5%) and student-student interactions (50%). The NAVID system was easier to use than the online video lectures. The online classes were less successful in building student-tutor interactions compared with in-person classes. The NAVID system received more scores in fulfilling the students’ expectations about the quality of conveying the concepts and learning. Conclusion The sudden shift from in-person to distance learning has caused some educational problems and lowered the student-student and student-tutor interaction quality. However, optimizing the infrastructure and necessary facilities for online education would help obviate the students’ academic needs.